Cellulose nanocrystal-reinforced poly(5-triethoxysilyl-2-norbornene) composites. Issue 2 (25th September 2019) - Hendren, Keith D.; Higgins, Morgan A.; Long, Brian K.; Foster, E. Johan
Abstract : We demonstrate the reinforcement of a previously inaccessible norbornene-silane with a stiff, bio-based nanofiller. Abstract : We demonstrate the reinforcement of a previously inaccessible norbornene-silane with a stiff, bio-based nanofiller. Poly(5-triethoxysilyl-2-norbornene) (PTESN), a glassy and thermally stable polymer, was combined with cellulose nanocrystals (CNCs) and solvent cast from toluene to form reinforced materials. Composite films showed excellent translucency and no visible aggregation, which was supported by scanning electron micrographs that showed no signs of CNC aggregation within the polymer matrix. Reinforcement was evident at the moderate loading of 5 wt% CNC, showing a statistically significant enhancement for Young's modulus and even greater reinforcement for 20 wt% CNC loading for Young's modulus (540 MPa vs. 970 MPa) and storage modulus at 25 °C (400 MPa vs. 1200 MPa). We suspect that there is a strong interaction between the polymer and CNC filler based upon the increase of thermal degradation temperature of the CNCs increasing, for example from 278 °C to 295 °C at 10 wt% CNCs. These interactions were probed via solid-state NMR, which suggests that no covalent bonding occurs between the triethoxylsilyl substituents of the polymer and the CNCs. We therefore hypothesize that hydrogen bonding interactions between PTESN and CNCs are responsible for the increased thermal stability and reinforcement of the polymer material.